The challenges of developing a contrast-based video game for treatment of amblyopia - Hussain, Zahra; Astle, Andrew T.; Webb, Ben S.; McGraw, Paul V. (Frontiers in Psychology, 2014)
Perceptual learning of visual tasks is emerging as a promising treatment for amblyopia, a developmental disorder of vision characterized by poor monocular visual acuity. The tasks tested thus far span the gamut from basic psychophysical discriminations to visually complex video games. One end of the spectrum offers precise control over stimulus parameters, whilst the other delivers the benefits of motivation and reward that sustain practice over long periods. Here, we combined the advantages of both approaches by developing a video game that trains contrast sensitivity, which in psychophysical experiments, is associated with significant improvements in visual acuity in amblyopia. Target contrast was varied adaptively in the game to derive a contrast threshold for each session. We tested the game on twenty amblyopic subjects (ten children and ten adults), who played at home using their amblyopic eye for an average of 37 sessions (approximately 11 hours). Contrast thresholds from the game improved reliably for adults but not for children. However, LogMAR acuity improved for both groups (mean: 1.3 lines; range: 0-3.6 lines). We present the rationale leading to the development of the game and describe the challenges of incorporating psychophysical methods into game-like settings.